Bilateral orbital plasmacytomas as first sign of extramedullary progression post CAR-T therapy: case report and literature review - Nogués-Castell, Javier; Feu-Basilio, Silvia; Felguera García, Óscar; Fernández de Larrea, Carlos; Oliver-Caldés, Aina; Balagué Ponz, Olga; Fassi, Jessica Matas (Frontiers in Oncology, 2023)
Background: Plasma cell leukaemia is an aggressive and rare form of plasma cell dyscrasia characterised by peripheral blood expression, poor prognosis, and high relapse rates. Extramedullary plasmacytomas are common in this entity and can affect various organs and soft tissues. Chimeric Antigen Receptor (CAR) T therapy is a novel immunotherapy for haematological malignancies with promising results. However, it is not indicated for plasma cell leukaemia and experience in this condition is limited. This case is a rare presentation of bilateral orbital plasmacytomas after CAR-T therapy in a patient with plasma cell leukaemia history. Case Presentation: We present the case of a 51-year-old female patient with a history of previous primary plasma cell leukaemia (PCL) treated with CAR-T therapy achieving complete response and without evidence of systemic progression. Six months after the treatment, she developed subacute proptosis and ptosis on the left eye. An orbital CT scan was performed and showed an orbital tumour in both eyes. A surgical biopsy with histological examination revealed plasma cells, consistent with a plasmacytoma. PET-CT and MRI confirmed the presence of tumours in both orbits. The patient was treated with dexamethasone and chemotherapy along with palliative radiation therapy to the left orbit which had a good response. Conclusion: Orbital involvement in multiple myeloma and PCL is rare, being plasmacytomas more common in other parts of the body. In this report, we present a case of a patient with PCL history, treated with multiple therapeutic lines including CAR-T therapy, who presented bilateral orbital plasmacytomas as the first sign of extramedullary progression after the treatment. This case should be considered by specialist in order to be aware that the orbits are a possible location of extramedullary progression.